The nucleotide sequence of a major glycine transfer RNA from the posterior silk gland of Bombyx mori L. - Zúñiga, M C (1977)
The nucleotide sequence of tRNA1Gly isolated from the posterior silk gland of Bombyx mori has been determined. This transfer RNA is present in high amounts in the posterior silk gland during the fifth larval instar. It has a GCC anticodon, capable of decoding a major glycine codon in the fibroin messenger RNA, GGU. Structural features of Bombyx tRNA1Gly and its homology to other eukaryotic glycine tRNAs are discussed.